THE EFFECTIVENESS OF DIGITAL STORYTELLING ON STUDENTS’ SPEAKING ABILITY - Andi Idayani (Lectura : Jurnal Pendidikan, 2019)
Speaking is an assential skill that used be mastered by the Students, because it is necessary for them to improve their ability to communicate orally by presenting their ideas and opinions in real life. Digital storytelling is the practice of using computer-based tools to tell stories. It can be used as homework, classroom group projects, or a holiday project for students. In relation to this, the purpose of the research is to find out is there any significant effect of digital storytelling on students’ speaking ability. Then, Describing and analyzing the effectiveness of digital storytelling in enhancing students’ speaking ability. in this study, the researcher used experimental research. An experimental usually involves two groups of subject, an experimental group and a control group. The population of this research was the fifth semester of English students of FKIP - Islamic University of Riau in academic year 2018/2019. The sampling technique used in this research is purposive sampling. The researcher choose 5B as experimental class which consist of 26 students and 5C as control class which consist of 25 students. The reseracher used speaking test as instrument which included in pre-test and post-test. The results of the research revealed that ttest > ttable (14,402>2.05954), ttable on degree freedom (df) 25 on the level of significant 0.05. Consequently, it means that the alternative hypothesis is accepted while the null hypothesis is rejected. So, the conclusion of the research has shown that there is positive effect of digital storytelling towards students’ speaking ability.